2015
DOI: 10.1530/rep-14-0517
|View full text |Cite
|
Sign up to set email alerts
|

Role of androgens in normal and pathological ovarian function

Abstract: Androgens mediate their actions via the androgen receptor (AR), a member of the nuclear receptor superfamily. AR-mediated androgen action is essential in male reproductive development and function; however, only in the last decade has the suspected but unproven role for AR-mediated actions in female reproduction been firmly established. Deciphering the specific roles and precise pathways by which AR-mediated actions regulate ovarian function has been hindered by confusion on how to interpret results from pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 234 publications
(271 reference statements)
1
99
1
10
Order By: Relevance
“…*P < 0.05; **P < 0.01. Walters 2015), including pGCs (Durlej et al 2011); however, no study to date has examined regulation of FSHR expression via AR in GCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*P < 0.05; **P < 0.01. Walters 2015), including pGCs (Durlej et al 2011); however, no study to date has examined regulation of FSHR expression via AR in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…FSH can synergize with androgens to regulate FSHR expression in follicles (Sen et al 2014, Walters 2015. Previous studies have shown that low-to-moderate doses of testosterone, a principal androgen, significantly increase FSHR mRNA levels in human luteinized GCs, whereas higher doses of testosterone do not further increase the FSHR mRNA levels and have no effect on FSHR protein expression (Garcia-Velasco et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…If Akr1c14 is not expressed, excessive androgens would accumulate in preovulatory follicles and thus affect the ovulatory process. Indeed, in vivo administration of DHT to immature female rats at the time of hCG injection reduces the ovulation rate [7]. The importance of 3α-HSD/ Akr1c14 in the removal of excessive androgens is well documented in the prostate [12] and liver [11].…”
Section: Figmentioning
confidence: 99%
“…Dihydrotestosterone (DHT) at a dose of 0.25 mg/kg, but not 25 mg/kg, improved the ovulatory response to superovulation in mice [6]. Conversely, DHT at a dose of 1 mg/kg decreased ovulation rates in immature rats, implying that optimal levels of androgens are required to maintain normal ovulatory function [7]. Excessive androgen signaling may lead to abnormal follicle growth.…”
mentioning
confidence: 99%
“…Андрогены уже на начальных этапах участвуют в процессе фолликулогенеза, рецепторы к ним обнаруживаются в первичных фолликулах при вовлечении их в растущий пул и далее на всех этапах созревания. Так, в преантральных фол-ликулах рецепторы к андрогенам экспресси-руются клетками гранулезы, тека-клетками и ооцитами [40,41]. Также описана экспрессия андрогеновых рецепторов и в клетках стромы яичника, особенно выраженная вокруг неболь-ших растущих фолликулов [42].…”
unclassified